Gutiérrez Gómez, Edgar (2012). The absurdity of life. Ayacucho (Peru): copyist Bautista, 129 pp. - Paz y Miño Conde, Manuel Abraham (2019)
Like any human expression, the meaning of life can be approached in an optimistic or pessimistic way. On the first mode, we have the books of: a) John A. Mackay, Scottish Presbyterian philosopher and theologian, The Meaning of Life and Other Essays of 1978 (3rd ed. ), where he actually talks about the meaning of manhood, vocation, truth, friendship, the universe and Christianity; the autobiographical book by Moisés Chávez Ramos, writer and evangelical Hebraist, Philosophy of Life (n/d) where he conceives life "as the search for the purpose and meaning of life" (p. 7). b) Ángel Peña Benito, Augustinian priest, Vale la pena la pena vivir (2006), who affirms that "(t)he meaning of life is in God, who loves us, even if, at times, it is hidden and silent" (p. 4).